Instep kicking accuracy based on playing positions among male UiTM Pahang football players / Mohd Azizi Ishak - Ishak, Mohd Azizi (Faculty of Sport Science and Recreation, 2015)
Kicking accuracy is an important component of soccer performance. It is the component of football performance that can be measured discretely and making it a good for performance research. The objective of this study is to compare the instep kicking accuracy based on playing position among male football players. All the subjects for this research were 18 subjects (N=18), which were divided between defenders (N=6), midfielders (N=6) and forwards (N=6). We constructed a plywood target measuring 243.5cm wide x 122cm high. Carbon paper applied to the surface of the target allowed measurement from a bull's-eye to 10 ball marks left by kicks. The results showed that the mean of defenders (35.50±1.05), midfielders (31.67±1.51), and forwards (37.50±1.05). There were significant differences in instep kicking accuracy between playing positions among male football players, which are the value (p<O.05). Hence, the instep kicking accuracy between playing position absolutely have a differences. In conclusion, midfielders are more accurate, so that midfielder's position is better than others when to take a penalty or free kicks. Hence, the instep kicking accuracy can be improved by using this testing design as a training session